Andrew Lenard: A Mystery Unraveled - Praught, J.; Smirnov, R.G. (Symmetry, Integrability and Geometry: Methods and Applications, 2005)
The theory of bi-Hamiltonian systems has its roots in what is commonly referred to as the “Lenard recursion formula”. The story about the discovery of the formula told by Andrew Lenard is the subject of this article.